Bioplastics from orange processing byproducts by an ecoefficient hydrothermal approach - Santos, Leticia B. [UNESP]; Silva, Rodrigo D.; Alonso, Jovan D. [UNESP]; Brienzo, Michel [UNESP]; Silva, Natalia C.; Perotto, Giovanni; Otoni, Caio G.; Azeredo, Henriette M.C. (Elsevier, 2023)
Valorization of orange processing byproducts into bioplastics represents a sustainable alternative to virgin plastics for some applications. In this study, we obtained three films based on such biomass, namely, orange peel (OPe), orange pomace (OPo), and a combination of peel, pomace, and finisher pulp (OPPP). The byproducts were submitted to a “clean” hydrothermal pretreatment at 121 °C for 30 min at 1.2 kgf.cm−2. They were then added with glycerol, homogenized, cast into films, and dried. The OPe film presented higher water vapor permeability and poorer overall tensile properties compared to the other films, possibly due to the lower polysaccharide contents in the peel compared to those in the pomace. The OPPP film was considered the most interesting from a biorefinery perspective since it is made from three orange processing byproducts instead of only one. Moreover, all films exhibited high antioxidant and UV-absorption capacities, indicating their potential applicability as active packaging materials for oxidizable products.
Keywords: Biorefinery; Citrus; Film; Food loss; Lignocellulose; Upcycling